PENDEKATAN DIAGNOSTIK DAN TERAPI DIARE KRONIS - Wiryan, NGP Cilik; Wibawa, I Dewa Nyoman (journal of internal medicine; Vol. 8, No. 1 Januari 2007)
Diarrhea is defined as a change in bowel habit, with an increase in stool frequency or fluidity or both, more than 3 times daily or stool weight > 200 g/day. Acute diarrhoe if it is less than 2 weeks of duration, persistent if between 2-4 weeks in duration, and Chronic if it is more than 4 weeks in duration. Diarhoea is a common problem around the world. Chronic diarrhea morecompleks about diagnosis and treatment than acute one. The pathophysiiological mechanisms chronic diarhoea divided into major group osmotic, secretory and imflamtory. A carefull history will often suggest the diagnosis and direct investigations. Physical examination more usefull to measure the severity of diarhoe rather than suggest the cause of chronic diarhoea. Iinitial investigation include blood test, serology for celiac ds, stool examinations. Small intestinal and colon ds need for enteroscopy, capsul endoscopy, sigmoidoscopy, colonoscopy, many test for non invasive for malabsorption. In specific clinical conditions need specific examination too. Small Intestinal Bacterial Overgrowth can be diagnosed directly by culture from aspiration of duodenal fluid or indirectly by using breath test. Bile acid malabsorption can be diagnosed by by measured bile acid radioactif labelled measured of metabolite serum, and bile acid excretion. Lactose malabsorption can be diagnosed by lactose assay, breath test (hydrogen 14C Lactose and 13 C lactose). Increasing orocaecal transit time diagnosed by using barium study, radionucleide scintygraphy, lactose hydrogen breath test. Chronic diarrhoea due to increasing hormones producing tumours diagnosed by measured increasing level of hormones in to serum. Investigations patients with chronic diarrhoea available in the ambulatory or hospitalised patients. Treatment of chronic diarrhoea depends on the specific aetiology and may be curative, suppressive or empirical.
Keywords: chronic diarrhea, diagnostic aproach